Recent advances in nanotechnology for Parkinson’s disease: diagnosis, treatment, and future perspectives - Yadav, Virendra Kumar; Dhanasekaran, Seshathiri; Choudhary, Nisha; Nathiya, Deepak; Thakur, Vishal; Gupta, Rachna; Pramanik, Sheersha; Kumar, Pankaj; Gupta, Nishant; Patel, Ashish (Frontiers in Medicine, 2025)
Parkinson’s disease is a progressive neurodegenerative disease that destroys substantia nigra dopaminergic neurons, causing tremors, bradykinesia, rigidity, and postural instability. Current treatment approaches primarily focus on symptom management, employing pharmacological, non-pharmacological, and surgical methods. However, these treatments often result in fluctuating symptoms, side effects, and disease progression. Here, the authors have reviewed the emerging field of nanomedicine as a promising path for Parkinson’s disease treatment, emphasizing its potential to overcome the limitations of traditional therapies. Nanomedicine utilizes nanoparticles for targeted drug delivery, leveraging their small size and high surface area to volume ratio to cross the blood-brain barrier and deliver therapeutic agents directly to affected brain regions. Various nanoparticles, including lipid-based, polymeric, metallic, and carbon-based, have shown potential in Parkinson’s disease treatment. Additionally, nanocarrier systems like liposomes, nanogels, dendrimers, and solid lipid nanoparticles offer controlled and sustained release of therapeutic agents, enhancing their bioavailability and reducing side effects. This review provides insights into the pathophysiology of Parkinson’s disease, highlighting the mechanisms of neurodegeneration, the role of alpha-synuclein, and the disruption of dopaminergic pathways. It further discusses the application of gene therapy in conjunction with nanomedicine for targeted therapeutic interventions.